Interdyscyplinarne, sieciowo-systemowe podejście do procesu readaptacji i reintegracji społecznej osób skazanych i ich rodzin - Nowak, Beata Maria (Studia Edukacyjne, 2020)
The author presents a holistic, network and systemic approach to the provision of assistance and support for individuals who are marginalised, at risk of exclusion and excluded. The author sees the adaptation of the clustering idea and theory and the compatible coopetition strategy as a real chance for a breakthrough in thinking about social re-adaptation and reintegration and for an effective modernisation of an inefficient prevention and social rehabilitation system.